The evolution of Austrian economics : from Menger to Lachmann - Gloria-Palermo, Sandye (Routledge studies in the history of economics, 1999)
This book argues, against the dominant orthodoxy in the history of economic thought, for the originality of Carl Menger's contribution to the development of the Austrian school of economics. Situating the evolution of Menger's thought in the tradition of classical political economy, the author documents the emergence of a Mengerian logic and its contribution to the formation of a distinctly Austrian tradition of economics. In its bold elucidation of the shaping of a tradition in economic thought, Tradition and Innovation in Austrian Economics provides a fresh and challenging persp.